Artificial intelligence in physical education: a bibliometric and systematic review - Rahman, Arif; Islam, Syahrizal (Pedagogy and Psychology of Sport, 2026)
Background. The rapid development of artificial intelligence (AI) has significantly influenced various educational domains, including physical education. However, research on AI in physical education remains fragmented, and a comprehensive mapping of research trends, thematic structures, and future directions is still limited. Aim. This study aims to examine publication trends, intellectual structures, and the theoretical and practical implications of artificial intelligence research in physical education. Material and methods. A systematic literature review combined with bibliometric analysis was conducted in this study. The article selection process followed the PRISMA framework, and data were retrieved from the Scopus database for the period 2016-2025. A total of 170 articles that met the inclusion criteria were analyzed using VOSviewer to identify publication trends, leading journal sources, author productivity, and keyword co-occurrence networks. Results. The results indicate substantial growth in research output in recent years, demonstrating that artificial intelligence in physical education is a rapidly expanding, multidisciplinary research field. Dominant research themes include machine learning, deep learning, big data, virtual reality, and wearable technology, which are closely associated with teaching quality, learner motivation, and performance outcomes. Conclusions. In conclusion, artificial intelligence represents a significant and sustainable research direction in physical education, offering substantial potential to advance pedagogical innovation and evidence-based practice in future educational settings.